Istikhdāmu Lu’bati Charades li Ta’līmi al-Mufradāti fī Firqati al-Lughati al-‘Arabiyyati - Boby Ghufron; Muassomah Muassomah; Moh. Fairus Sholeh; Moch Fikri Abdul Aziz (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2023)
In extracurricular language activities, memorising foreign vocabulary is often only required. This seems monotonous and makes the participants bored with learning. This study aims to explore vocabulary learning activities using the Charades game and participants' responses related to it. This type of research is a descriptive qualitative method with observation and documentation as an instrument for collecting data. Data analysis techniques with the Miles and Huberman model; data reduction, data display, and conclusions. This research shows that this game contributes theoretically and practically to the research. In theory, picture guessing is an attractive, easy, and straightforward game with positive results in vocabulary learning activities. In practice, there are five steps to the game; 1) dividing participants into two teams, 2) writing vocabulary, 3) flipping coins, 4) demonstrating vocabulary, and 5) adding up all points. Positive responses were obtained from the questionnaire given to 20 participants in the form of vocabulary learning with the Charades game was more interesting, more accessible, and more transparent and could increase motivation to learn vocabulary. Researchers hope the Charades game could further use better learning media and tutors can condition participants in larger groups.